Behavioural aspects of decision-making and its application in Poland illustrated by the example of the public institutions - Dąbrosz-Drewnowska, Paulina (Procedia computer science, 2021)
The development of behavioural economics influenced significantly the progress of studies related to decision making. The acquis of behavioural economics could be used in the public sector worldwide and they are applied more commonly in public politics. In practice, as its proved globally, the cosmetic changes supported by the behavioural knowledge help administration work efficiently without making big reforms, financial or organizational costs. Those changes go together with the knowledge development of behavioural economics and thanks to the growing number of studies related to the exploitation of behavioural techniques in the public institutions around the world. The same situation is observed in the public institutions in Poland where the behavioural techniques are being applied. The article shows how the subject related knowledge is practiced in Polish public sector basing on The Polish Economic Institute’s report "Simpler, cheaper and more effective, in other words, how behavioural economics supports public policies in Poland". This report is an introduction to studies in this area. It shows that some behavioural techniques are used more often while others are rarely applied in Polish public sector. The article analyzes why the behavioural techniques in Poland are still rarely applied. It proposes solutions which could help to create the strategic behavioural public policy, following the example of other countries, first of all the necessity of strict cooperation of the Polish public sector with behavioural economics study experts and centers located in Poland and abroad. It would allow to know better new methodological approaches of behavioural public sector in the world to design and test interventions in Poland.